Major markets for hides, skins and leather in Western Europe (Geneva: International Trade Centre, 1968)
The book is centered on the major markets for hides, skins and leather in Western Europe. In preparation for this survey a large number of enquiries were made in the selection of ten markets. The survey covers production and processing of hides and skins in developing countries, as well as export promotion and marketing.
rpm 22/01/2019
Loans
Keywords: Hides; Skins; Leather; Western Europe